Lip Thickness with Tongue Space Area Assessment By Cephalometric Analysis for Iraqi Adult Sample with Class II Dental and Skeletal Pattern - Laith Hamood AL-Salmany1 , Zena Hekmat Altaee1 , Ahmed Jassam Al-Naqeeb 2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: With different skeletal classes, there may be some variability among the lip thickness andtongue space area that could be the causative factor for skeletal malrelationship so that this study was aimedto determine the tongue and the available boundary space area with lip thickness and correlate them togetherin sample with class II skeletal pattern.Methods: Seventy Iraqi adult subjects (32 males and 38 females) with cl II skeletal pattern who haveincreased over jet and ANB angle greater than four degrees. The cephalometric measurements include upperand lower lip thicknesses with height and length of tongue and position of tongue base and hyoid bonefrom the cervical line. The cephalograms were analyzed using AutoCAD program to measure demandedareas. Results: This study revealed that a significant gender difference was found between T-Area, V-TT,TH, V-FP, AH-CL, AH-FP, and upper and lower lip thickness in which higher mean value in males thanfemales. The correlation between all the measured variables of present sample with SNA, SNB and ANBangles a non-significant difference was found except for V-CL which shows significant difference. Strongcorrelation was found among the T-Area with V-TT, TH, V-FP, AH-CL, AHFP, upper lip thickness and lowerlip thickness.Conclusions: In skeletal class II, the associated cranial base angles shows independent association from theboundary soft tissues so that these variations not always contribute to be the causative factor for skeletaldisharmony